Religion and the Sustainable Development Goals - Tomalin, Emma (The review of faith & international affairs, 2019)
Religion is a major cultural, social, political, and economic factor in many official development assistance (ODA) recipient countries. After decades of being ignored by global development processes, greater portions of development aid are now channeled via faith-based organizations, and religion is increasingly recognized as a human resource rather than just an obstacle to development. This essay explores the role that faith actors are playing in the Sustainable Development Goals process. It is based upon findings from a research project funded by the UK Arts and Humanities Research Council (AHRC)-"Keeping Faith in 2030: Religions and the SDGs."